2020
DOI: 10.1200/jco.20.00491
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Combination Obinutuzumab, Ibrutinib, and Venetoclax in Treatment-Naïve and Relapsed or Refractory Chronic Lymphocytic Leukemia

Abstract: PURPOSE The development of highly effective targeted agents for chronic lymphocytic leukemia offers the potential for fixed-duration combinations that achieve deep remissions without cytotoxic chemotherapy. PATIENTS AND METHODS This phase II study tested a combination regimen of obinutuzumab, ibrutinib, and venetoclax for a total of 14 cycles in both patients with treatment-naïve (n = 25) and relapsed or refractory (n = 25) chronic lymphocytic leukemia to determine the response to therapy and safety. RESULTS T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 44 publications
1
55
0
Order By: Relevance
“…mutated IGHV genes), the chemoimmunotherapy combination regimen consisting of fludarabine, cyclophosphamide, and rituximab (FCR) allows the achievement of undetectable minimal residual disease and long-term remissions (18). More recently, combinations including multiple targeted drugs with a different mechanism of action, such as BTK and Bcl-2 inhibitors with or without anti-CD20 monoclonal antibodies (mAb), have shown very promising results in terms of depth and durability of response, although data are not yet mature (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…mutated IGHV genes), the chemoimmunotherapy combination regimen consisting of fludarabine, cyclophosphamide, and rituximab (FCR) allows the achievement of undetectable minimal residual disease and long-term remissions (18). More recently, combinations including multiple targeted drugs with a different mechanism of action, such as BTK and Bcl-2 inhibitors with or without anti-CD20 monoclonal antibodies (mAb), have shown very promising results in terms of depth and durability of response, although data are not yet mature (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Roger et al tested the triplet regimen of ibrutinib, venetoclax, and obinutuzumab in patients with previously untreated and relapsed/refractory CLL 84 . This is another example of successful time-limited trial for a total of 14 cycles.…”
Section: Ibrutinib Combinationsmentioning
confidence: 99%
“…While more recently, ibrutinib and acalabrutinib have been tested within fixed-duration combinations, these combinations of novel agents are not yet approved. Hence, their main use remains as monotherapy that is given until disease progression or unacceptable toxicity [ 27 , 28 , 29 , 30 ]. Adding to the financial burden and side effects associated with an indefinite therapy, the continued exposure to BTKi seems to promote the acquisition of resistance mutations.…”
Section: Mechanisms Of Resistance To Btk Inhibitionmentioning
confidence: 99%
“…Venetoclax, a BH3 mimetic, has been developed to bind Bcl-2 at the same site as BH3-only proteins to effectively inhibit Bcl-2 [ 60 ]. After clinical studies in CLL have consistently shown impressive activity of venetoclax in all therapeutic settings as monotherapy as well as in combinations, it has been approved for the treatment of patients with previously untreated and relapsed/refractory CLL [ 7 , 8 , 27 , 28 , 29 , 30 , 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Mechanisms Of Venetoclax Resistancementioning
confidence: 99%
See 1 more Smart Citation